Impact of drought on economy: a district level analysis of Madhya Pradesh, India. Issue 6 (12th May 2021) - Sharma, Ashish; Sen, Subir
Abstract : This study examines the consequences of droughts on the aggregate economic growth and the growth of agriculture, industry and service sectors respectively. The benefits of financial relief post-drought and the efficacy of irrigation infrastructure is also statistically tested considering a sample of 45 districts in one of the largest states in India, Madhya Pradesh. A two-step GMM procedure is applied to balanced panel data for the period 2005 to 2012. Districts in the state face recurrent droughts, limited irrigation, and rainfall variability increases vulnerability to drought risks. Results show that drought adversely impacts on the growth rate of the agricultural sector and the aggregate economy. Post-drought financial relief has a positive and significant impact on the growth rate of the industrial sector and economic growth at the district level. The study contributes to the growing literature on disaster impact on growth by focusing on district-level assessment.